2006
DOI: 10.1167/iovs.05-1102
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Capability of Optical Coherence Tomography in Evaluating the Degree of Glaucomatous Retinal Nerve Fiber Damage

Abstract: RNFL thickness measured on OCT may serve as useful adjuncts in accurately and more objectively distinguishing normal from glaucomatous eyes, even in the early stages of glaucoma and may help to differentiate various severities of glaucoma. Average and inferior RNFL thicknesses are among the most efficient parameters for distinguishing such a differentiation. RNFL thicknesses in eyes blinded by glaucoma provide an estimate of the component of the RNFL thickness, which is not related to visual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
128
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 205 publications
(143 citation statements)
references
References 19 publications
14
128
1
Order By: Relevance
“…In the fellow eyes, no significant difference in RNFL measurement was found except the temporal quadrant when compared with the controls. This result is comparable with our study Sihota et al (5) evaluated the role of (OCT) in detecting differences in peripapillary RNFL thickness among normal and glaucomatous eyes and also among different severities of glaucoma. The average RNFL in control subjects, early glaucoma, moderate glaucoma, severe glaucoma, and blind glaucoma were 102.30 plus/minus 10.34, 77.68 plus/minus 15.7, 66.07 plus/minus 15.5, 53.65 plus/minus 14.2, and 44.93 plus/minus 4.95 micron, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…In the fellow eyes, no significant difference in RNFL measurement was found except the temporal quadrant when compared with the controls. This result is comparable with our study Sihota et al (5) evaluated the role of (OCT) in detecting differences in peripapillary RNFL thickness among normal and glaucomatous eyes and also among different severities of glaucoma. The average RNFL in control subjects, early glaucoma, moderate glaucoma, severe glaucoma, and blind glaucoma were 102.30 plus/minus 10.34, 77.68 plus/minus 15.7, 66.07 plus/minus 15.5, 53.65 plus/minus 14.2, and 44.93 plus/minus 4.95 micron, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…A negative correlation was seen between the two and it was significant (r value > 0.5), which means as the severity of glaucoma increases there is a progressive decline in average RNFL thickness. Similar results were found in C. Ajtony et al 9 study and Sihota et al 13 study, but not that of Sujatha Subbaiah et al 7 study which showed a positive correlation between MD and average RNFL thickness (Table no. 2).…”
Section: Correlation Between MD and Average Rnfl Thickness And Comparsupporting
confidence: 80%
“…Previous studies [11][12][13][14][15][16] have reported the sensitivity and specificity of OCT for discriminating between healthy and glaucomatous eyes. Very few studies, [17][18][19][20][21] however, have attempted to increase the diagnostic ability of OCT using learning classifiers.…”
Section: Discussionmentioning
confidence: 99%